Analysing Finnish primary EFL textbooks through a Bangladeshi lens (Teacher’s World: Journal of Education and Research, 2023)
A closer examination of Finland’s exceptional educational achievement reveals that the country’s education system bears fruit from a concerted effort that places a premium on textbooks. With Bangladesh’s predominance of textbook-based methods, their Finnish counterparts appear critical in determining how textbooks can be bettered in offering young learners a more effective teaching-learning experience. This qualitative study applied deductive content analysis to examine five Finnish primary English as a foreign language (EFL) textbooks through a Bangladeshi lens. The analysis found that the textbooks in Finland used their native language, Finnish, to impart narrative-driven multimodal action-based English content as well as exercises. A highly visually rich textbook design accommodatively allowed different English learning approaches to merge with the Finnish teachers’ autonomous method of instruction. Though the size of the content and exercises are upwardly voluminous, they are presented in a way that comes across as very appealing to the children. The study also advises avenues Bangladeshi EFL textbooks should explore.Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.83-101